Functional composition in software-defined network based on atomic capacity - UANTong D; ANJu-long L; HENGGuo-zhen C; UYu-xiang H (Tongxin xuebao)
Software-defined network (SDN) enables frequent network functional innovation and evolution,making the control function modularity one of the most hot research fields on SDN.Aiming at network-wide functional composition based on unified module definition and function division,firstly,atomic capacity (AC) is introduced as atomic elements of module function division and an AC-based resource description method is proposed; secondly,functional composition module based on two-level mapping is put forward and a heuristic algorithm to calculate the composition is proposed; fi-nally,an AC-orchestrating layer as extended structure of SDN application layer is devised and then a NetFPGA-10G pro-totype implementation is given.Experimental results show that the method can combine functional instances more effec-tively with better resource utilization.